Lightning flowers : my journey to uncover the cost of saving a life - Standefer, Katherine E., 1985- (Little, Brown Spark, 2020)
What if a lifesaving medical device causes loss of life along its supply chain? That's the question Katherine E. Standefer finds herself asking one night after being suddenly shocked by her implanted cardiac defibrillator. In this gripping, intimate memoir about health, illness, and the invisible reverberating effects of our medical system, Standefer recounts the astonishing true story of the rare diagnosis that upended her rugged life in the mountains of Wyoming and sent her tumbling into a fraught maze of cardiology units, dramatic surgeries, and slow, painful recoveries. "--Dust jacket flap